Step‐by‐step protocol for the isolation and transient transformation of hornwort protoplasts - Neubauer, Anna; Ruaud, Stéphanie; Waller, Manuel; Frangedakis, Eftychios; Li, Fay‐Wei; Nötzold, Svenja I.; Wicke, Susann; Bailly, Aurélien; Szövényi, Péter (Applications in plant sciences, 2022)
Premise A detailed protocol for the protoplast transformation of hornwort tissue is not yet available, limiting molecular biological investigations of these plants and comparative analyses with other bryophytes, which display a gametophyte‐dominant life cycle and are critical to understanding the evolution of key land plant traits. Methods and Results We describe a detailed protocol to isolate and transiently transform protoplasts of the model hornwort Anthoceros agrestis. The digestion of liquid cultures with Driselase yields a high number of viable protoplasts suitable for polyethylene glycol (PEG)‐mediated transformation. We also report early signs of protoplast regeneration, such as chloroplast division and cell wall reconstitution. Conclusions This protocol represents a straightforward method for isolating and transforming A. agrestis protoplasts that is less laborious than previously described approaches. In combination with the recently developed stable genome transformation technique, this work further expands the prospects of functional studies in this model hornwort.